Upaya Pustakawan dalam Mendukung Keterbukaan Data Penelitian di Jurnal Ilmiah peringkat Sinta 1 di Universitas Gadjah Mada - Sri Junandi; Seno Yudhanto (Ikatan Pustakawan Indonesia, 2022)
Librarians have a significant role in publishing scientific journals. But on the one hand, scientific journals are also a means of ensuring the availability of research data for the public. This study aims to identify the policy of openness of research data and the efforts that can be made by librarians in scientific journals ranked SINTA 1 in the UGM environment. The research method used is qualitative research. The research was carried out in September 2022. Data collection techniques were in the form of virtual interviews, observation, and information retrieval on journal websites. Analysis and presentation of data was carried out descriptively based on coding according to the research objectives. The results obtained show that most of the scientific journals ranked SINTA 1 at UGM have a policy of openness to research data. Three journals that involve librarians in scientific journal activities are Indonesian Journal of Geography, Indonesian Journal of Chemistry and ASEAN Journal on Science and Technology for Development. The efforts that can be made by librarians are to be actively involved in the management of scientific journals, to be involved in the formulation of research data policies, and to be active in disseminating the importance of openness of research data in scientific journals. The conclusion hows the policy of openness of research data in scientific journals, especially at Gadjah Mada University has become an inseparable part that must be stated in the journal policy. Librarians as managers of scientific journals as well as information managers can play an active role in making research data openness policies.